PROBLEMS OF EVALUATING THE STATE OF THE ACCOUNTING SYSTEM AT THE CURRENT STAGE OF ECONOMIC REFORM - Kahharov Zuhriddin Zafarbek o'g'li (Journals Park Publishing, 2023)
In today's rapidly evolving business world, accounting plays a crucial role in ensuring the success of companies. Accounting systems help businesses to keep track of their financial transactions, cash flow, profits, and losses. However, in recent years, there have been concerns about the accuracy and reliability of accounting systems. Many companies have been accused of financial mismanagement and fraud, which has caused investors to lose confidence in their financial reports. This article will examine the problems of evaluating the state of the accounting system at the current stage of economic reform.
Keywords: accounting system, economic reform, evaluation problems, consistent standards, regulations, accounting infrastructure, technological integration.